Does climate change affect enterprises’ ability to sell their products? - Yu, Siming; Cai, Cheng; Zhang, Shuocheng; You, Peng (Frontiers in Ecology and Evolution, 2022)
Based on local cities’ climate change data and the operating income data of Chinese listed enterprises from 2008 to 2019, we study the impact of climate change on enterprises’ sales ability and analyze its subsequent influence on their sales revenue from three dimensions: inside enterprises, the supply side and the demand side. The results show that climate change reduces enterprises’ sales revenue. From enterprises’ internal perspective, climate change reduces production efficiency, increases management costs and the impact on the cost of sales is not obvious. From the demand side, climate change increases business risks and reduces transactions between large customers and enterprises. The share of sales from large customers is reduced, but no obvious impact is observed for small customers. On the supply side, climate change reduces business credit levels, which in turn reduces sales revenue. A heterogeneity analysis shows that the impact of climate change on sales revenue is more obvious in private enterprises, enterprises with weak internal controls and enterprises in central and western regions of China.